PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE KUIS TIM DALAM PEMBELAJARAN MATEMATIKA KELAS VII SMP NEGERI 1 BUKIT TINGGI - -, Nurrahmawati (Universitas Pasir Pengaraian, 2013)
The purpose of this study are to know How the activity of learning studentsthat appears during implemented strategy of learning active team type quiz and How the student learning outcomes after implemented of active learning strategies Team Type Quiz. The type of this study were a pra-experimental and descriptif study with The One Shot Case Study design. The study population was all grade VII students of Junior High School in Bukittinggi. The sample selectionis done by purposive sampling technique and was elected class VII SMP Negeri 1 Bukit Tinggi as research subjects. Instruments used for data collection were observation sheet student activity and achievement test in the form of an essay test. Dataobtained from observation sheets were analyzed using percentages, while the data obtained from the study were analyzed using a minimum completeness criteria (KKM). KKM that had been set up in SMP N 1 Bukit Tinggi is 67.